The glass ceiling perception and female teacher burnout: the mediating role of work–family conflict - Wei, Yun; Subramaniam, Geetha; Wang, Xueshen (Frontiers in Psychology, 2025)
IntroductionThis paper aims to investigate the mediating role of work–family conflict in the relationship between the perception of the glass ceiling and female teacher burnout. The glass ceiling can create significant career barriers for women, potentially increasing work–family conflict and, in turn, leading to higher levels of burnout. Exploring these dynamics can provide insights into the underlying mechanisms contributing to female teachers’ well-being and inform strategies to mitigate burnout in educational settings.MethodsThe sample population comprises 200 female teachers working in higher educational institutions in China where data has been collected via a survey questionnaire, followed by SPSS and Smart PLS to analyse and test the hypotheses.ResultsResults indicate that there is a positive relationship between the perception of glass ceiling, work–family conflict and female teacher burnout, and work–family conflict mediates the relationship between the perception of glass ceiling and female teacher burnout in higher educational institutions in China.DiscussionThese findings highlight how work–family conflict caused by the glass ceiling perception negatively impacts burnout among female faculty members in higher educational institutions, which are relevant to the UN Sustainable Development Goals (SDGs) 3, 4, and 5 emphasizing women’s well-being, high-quality education, and gender equality, it offers actionable suggestions for policymakers to reduce the incidence of female teacher burnout.